ANALISIS YURIDIS TERHADAP TINDAK PIDANA PASAL 372 KUHP: STUDI PUTUSAN NOMOR.55/PID.B/2019/PN.KBU - Ibrahim Fikma Edrisy (Universitas Muhammadiyah Kotabumi, 2020)
This study discusses the JURIDIC ANALYSIS OF CRIMINAL ACTS ARTICLE 372 of the Criminal Code (study of Decision No.55/Pid.B/2019/PN.Kbu), Methodology has many meanings, such as (a) the logic of scientific research, (b) the study of scientific processes and concepts. , and 9c) science and processes and procedures. Based on this, it can be interpreted that science is a simple tool in improving science and technology as well as art. Therefore, the research aims to present the facts in a systematic, methodological and consistent manner. Based on the description in the previous article, it can be concluded: a. the application of unlawful materials for the combination of embezzlement violations, serial number 55/Pid.B/2019/PN.Kbu in the author's opinion is correct and in accordance with the law. , both testified about the terms and conditions of the accused. And the judge upheld the claim that the defendant had been jointly charged with being a defendant and was threatened with punishment under Article 372 of the Criminal Code, a statement of Article 55.1 of the Criminal Code.